Extent of myosin penetration within the actin cortex regulates cell surface mechanics - Binh An Truong Quang (Nature Portfolio, 2021)
Cellular deformations are largely driven by contractile forces generated by myosin motors in the submembraneous actin cortex. Here we show that these forces are controlled not simply by cortical myosin levels, but rather by myosins spatial arrangement, specifically the extent of their overlap with cortical actin.